Impaired associative fear learning in mice with complete loss or haploinsufficiency of AMPA GluR1 receptors - Feyder, Michael; Wiedholz, Lisa; Sprengel, Rolf; Holmes, Andrew (Frontiers in Behavioral Neuroscience, 2007)
There is compelling evidence that L-alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) glutamate receptors containing the GluR1 subunit contribute to the molecular mechanisms associated with learning. AMPA GluR1 glutamate receptor knockout mice (KO) exhibit abnormal hippocampal and amygdala plasticity, and deficits on various assays for cognition including Pavlovian fear conditioning. Here we examined associative fear learning in mice with complete absence (KO) or partial loss (heterozygous mutant, HET) of GluR1 on multiple fear conditioning paradigms. After multi-trial delay or trace conditioning, KO displayed impaired tone and context fear recall relative to WT, whereas HET were normal. After one-trial delay conditioning, both KO and HET showed impaired tone and context recall. HET and KO showed normal nociceptive sensitivity in the hot plate and tail flick tests. These data demonstrate that the complete absence of GluR1 subunit-containing receptors prevents the formation of associative fear memories, while GluR1 haploinsufficiency is sufficient to impair one-trial fear learning. These findings support growing evidence of a major role for GluR1-containing AMPA receptors in amygdalamediated forms of learning and memory.